2011
DOI: 10.1111/j.1439-0272.2011.01268.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of alfuzosin and sildenafil combination in male patients with lower urinary tract symptoms

Abstract: Lower urinary tract symptoms (LUTS) and erectile dysfunction (ED) are frequently encountered in ageing males. We compared the efficacy of alfuzosin 10 mg alone or in combination with sildenafil 50 mg in the treatment of LUTS due to benign prostatic hyperplasia. One hundred male patients older than 45 years were randomized to two groups containing 50 patients each; one group receiving alfuzosin 10 mg and the other group alfuzosin 10 mg combined with sildenafil 50 mg. International Prostate Symptom Score (IPSS),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…No large double‐blind placebo‐controlled study has evaluated the combination of a PDE5 inhibitor and α‐blocker for the improvement in LUTS suggestive of BPH, but several small studies with few patients [40], unblinded designs [41], and short treatment periods [42] have suggested that some patients may experience some additive effect, clinical results consistent with our findings. However, other small studies could not identify any additive effect [43] or the data could not be interpreted [44]. On the other hand, considering both LUTS and sexual dysfunctions, a panel of experts recently suggested that combination therapy with PDE5 inhibitors and α 1 ‐adrenergic blockers would be superior to PDE5 inhibition alone [45].…”
Section: Discussionmentioning
confidence: 99%
“…No large double‐blind placebo‐controlled study has evaluated the combination of a PDE5 inhibitor and α‐blocker for the improvement in LUTS suggestive of BPH, but several small studies with few patients [40], unblinded designs [41], and short treatment periods [42] have suggested that some patients may experience some additive effect, clinical results consistent with our findings. However, other small studies could not identify any additive effect [43] or the data could not be interpreted [44]. On the other hand, considering both LUTS and sexual dysfunctions, a panel of experts recently suggested that combination therapy with PDE5 inhibitors and α 1 ‐adrenergic blockers would be superior to PDE5 inhibition alone [45].…”
Section: Discussionmentioning
confidence: 99%
“…Four trials ( n = 281) compared sildenafil combined with an AB versus AB monotherapy [4749,51]. Two 3-mo trials evaluated sildenafil combined with alfuzosin 10 mg versus alfuzosin monotherapy; one used daily sildenafil 25 mg [48] and the other used sildenafil 50 mg (dosing frequency not reported) [51].…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Two 3-mo trials evaluated sildenafil combined with alfuzosin 10 mg versus alfuzosin monotherapy; one used daily sildenafil 25 mg [48] and the other used sildenafil 50 mg (dosing frequency not reported) [51]. One 4-mo trial evaluated sildenafil 50 mg combined with doxazosin 2 mg versus doxazosin alone, but dosing frequency was not reported [47].…”
Section: Evidence Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…In the review by Trost et al [67], a pooled summary of all randomized, placebo-controlled trials evaluating 5-ARIs revealed slightly increased rates over placebo Placebo effects in studies are shown in parenthesis. Data from Gur et al [66] we found 16 RCTs on tadalafil [184,185,187,188,[192][193][194][195][198][199][200][201][202][203][204][205], 3 RCTs on sildenafil [183,191,196], 2 RCTs on vardenafil [186,197] and 2 RCTs on UK-369,003 [189,190]. The PDE5 inhibitors are used alone or in combination mostly with α-blocker alfuzosin or tamsulosin.…”
Section: Silodosinmentioning
confidence: 99%